2022
DOI: 10.9767/bcrec.17.2.13712.363-374
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Zinc Oxide Supported on Gelatin Mesoporous Silica (GSBA-15) on Structural Character and Their Methylene Blue Photodegradation Performance

Abstract: Gelatin mesoporous silica SBA-15 (GSBA-15) with rod-like morphology has been successfully synthesized by hydrothermal method using P-123:gelatin, then aged at 90 °C for 24 h and calcined at 550 °C for 5 h. GSBA-15 was impregnated with ZnO amounts of 1; 5; and 10 wt% to obtain Zn/GSBA-15. Samples were characterized by X-ray Diffraction (XRD), Fourier Transform Infra Red (FTIR), Scanning Electron Microscopy (SEM), and Brunauer-Emmett-Teller (BET). The efficiency of methylene blue photodegradation was determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…One of the developments in dye treatment is via the combination of adsorption-photodegradation processes [ 4 , 5 ]. Several studies reported using SBA-15 and silica combined with carbon nitride or titania as an efficient photocatalyst for dye removal [ 4 , 6 , 7 , 8 , 9 ]. The method offers simultaneous adsorption of pollutants followed by photodegradation under light irradiation to decompose the adsorbed pollutants into less harmful molecules [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the developments in dye treatment is via the combination of adsorption-photodegradation processes [ 4 , 5 ]. Several studies reported using SBA-15 and silica combined with carbon nitride or titania as an efficient photocatalyst for dye removal [ 4 , 6 , 7 , 8 , 9 ]. The method offers simultaneous adsorption of pollutants followed by photodegradation under light irradiation to decompose the adsorbed pollutants into less harmful molecules [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mesopore silica with gelatin as the cotemplate (GSBA-15) was prepared by following the previous study with a P123:gelatin ratio of 1:0.01 (%w/w) [23]. The incorporation of iron oxide into GSBA-15 was done by mixing H2O, Fe(Cl)6.6H2O, and GSBA-15 with a ratio of 2:10:100 (%w/v/w), respectively.…”
Section: Synthesis Of Fe2o3/gsba-15mentioning
confidence: 99%
“…Characterization was done using FTIR spectrophotometer (Nicolet 6700-Thermo Fisher Scientific), XRD (Philips X'pert, Cu-Ka 0.04 o and counting time of per 10 s, 2θ 5-80•), SEM (ZEISS EVO MA and J-image (BSD-2 license) to count the number of particles, measure their size and calculate the average size of the SEM image data), and surface area analyzer (NOVA in-struments© 1994-2010 Quantachrome Instruments version 11.0). The crystal size of gelatin mesoporous silica GSBA-15 and Fe2O3/GSBA-15 was calculated with the Debye Scherrer formula [23] as Equation 2.…”
Section: Characterizationmentioning
confidence: 99%
See 1 more Smart Citation